1986
DOI: 10.1021/bi00368a051
|View full text |Cite
|
Sign up to set email alerts
|

Location of the sites of reaction of N-ethylmaleimide in papain and chymotryptic fragments of the gizzard myosin heavy chain

Abstract: The thiol of the gizzard myosin heavy chain, which reacts most rapidly with N-ethylmaleimide (MalNEt), has been located in the subfragment 2 region of myosin rod by fragmentation of [14C]-MalNEt-labeled myosin with papain and chymotrypsin. MalNEt reacts more slowly with thiols present in the 70- and 25-kilodalton (kDa) papain fragments of subfragment 1. The reaction of MalNEt with thiols present in these regions is increased on addition of ATP by factors of 2 and 10, respectively, when myosin is modified in 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Although the actin-activated Mg2+-ATPase was three times higher than that with unlabeled, unphosphorylated myosin, the degree of activation by actin filaments was reduced for the fluorescent myosin. These observations were again consistent with the labeling of the SH-C group (Onishi, 1985;Nath et al, 1986).…”
Section: Characterization Of Fluorescently Labeled Myosinsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the actin-activated Mg2+-ATPase was three times higher than that with unlabeled, unphosphorylated myosin, the degree of activation by actin filaments was reduced for the fluorescent myosin. These observations were again consistent with the labeling of the SH-C group (Onishi, 1985;Nath et al, 1986).…”
Section: Characterization Of Fluorescently Labeled Myosinsupporting
confidence: 88%
“…Proteolytic analyses indicated that the tetramethylrhodamine groups were associated primarily with the SH-B of the 17-kD light chain, and the SH-C group of the heavy chain near the COOH terminus of the S1 head (Nath et al, 1986). While important characteristics of myosin, including selfassembly and actin-activated ATPase activities, were preserved qualitatively after fluorescent labeling, there were quantitative changes similar to those induced by other sulfhydryl reacting agents (Onishi, 1985;Chandra et al, 1985;Nath et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Constructs of SMM with altered regulation typically have abnormally high ATPase activities in the unphosphorylated state and an abnormally low ATPase in the phosphorylated state (36,(42)(43)(44)(45)(46)(47). Alkylation of SMM thiols causes a similar effect (41,48,49) most likely attributed to reaction of SH1(Cys 717 ). The effects of H 2 O 2 on pHMM and upS1 were very similar in our studies, suggesting that they are not mediated by modification of the most reactive thiol on SMM, which is in the S2 region of the rod (Cys 892 ) (49) and which is not present in S1.…”
Section: Discussionmentioning
confidence: 99%
“…Four antibodies with epitopes in the central portion of therod ($2.1, $2.2, LMM.1, and LMM.2) bind tightly to synthetic filaments and block their disassembly to the folded monomer in the presence of MgATE The stabilization is probably due to a physical cross-linking between myosin molecules in the filament. Alternatively, antibody binding could induce a change in the myosin that mimics phosphorylation, although only modifications to the head have been observed to have this effect (Nath et al, 1986).…”
Section: Discussionmentioning
confidence: 99%